Aplicação condensada das três primeiras fases do PECS em uma menina com transtorno do espectro do autismo - Manzini, Ana Carolina Gurian (Universidade Federal de São Carlos, 2019)
Introduction: Children with Autism Spectrum Disorder (ASD) may have difficulties in the use of oral communication and may benefit from teaching programs focused on this ability. The literature has pointed benefits to the use of The Picture Exchange Communication System (PECS) better known as the Figure Exchange Communication System for Children with Autism Spectrum Disorder. Objective: To analyze the effects of condensed application of the first three phases of PECS on the emergence of new picture exchange responses in autism spectrum disorder in a natural context. Method: Participated in this study a child with speechless ASD, aged six years. The survey was conducted at the participating child's home. The following data collection instruments were used: Interview script to identify the participant's favorite items; Test to evaluate preference, Session registration protocol. The ABA design was used among participants with the baseline, teaching (intervention) and baseline step. Results: The results showed that at baseline the child's performance was null, that is, she had no knowledge of the use of PECs. After the implementation of the teaching / intervention, despite some partial and / or total physical aids, the child was able to exchange pictures for the desired food. Conclusion: The strategies of condensing the three phases of the PECS adopted viable in the home context and provided for the child and their communication partners effective learning about the use of alternative communication.
Condensed application of the three first phases of PECS in a girl with autism spectrum disorder
Keywords: Educação especial; Transtorno do espectro do autismo; Picture exchange communication system; Special education; Autism spectrum disorder; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO